Tutees' Bullying Experiences in Employment of Pair Tutoring: A View from Grade Two Pupils - Margarita V. Jaminal (EduLine: Journal of Education and Learning Innovation, 2024)
Bullies can victimize others in a multitude of ways. While some are hidden and private, others are obvious and public. Bullying in schools frequently takes place in unstructured learning environments. Direct bullying combines verbal and physical abuse. Verbal bullying occurs when a pupil is the target of remarks made aloud or information written that harms their feelings. This exploratory research study was to identify the experiences of bullying by tutees.The research sample comprised fifteen tutees at the Division of Misamis Oriental at the Tagoloan Central School, Philippines. Using the qualitative approach with an exploratory research design, the fifteen grade two tutees who experienced bullying inside the classroom during pair tutoring sessions were considered participants through purposively sampled selection. There was the utilization of in-depth interviews in the data gathering. The study adhered to ethical principles during the conduct. It strictly followed the components of trustworthiness: credibility, dependability, transferability, and conformability to review the validity of the qualitative data. The study revealed that during pair tutoring, tutees experienced verbal bullying- the tutor to the tutee as the tutor constantly uses mean remarks, such as You are dull. Relationship bullying to the tutee as the tutor becomes bossy and short-tempered by letting tutees learn quickly. Physical bullying to the tutee as the tutor eventually hits the tutee if the tutee cannot learn quickly. Along with the insights, the study emphasized that teachers must closely monitor by observing tutor behavior and words they utter during pair torturing sessions and select and train tutors; training should cover tutor roles and responsibilities so that bullying will not occur during pair tutoring sessions and bullying is an issue in education that needs to be solved to ensure pupils good learning outcomes by a safe learning environment. Bullying affects children's academic achievement because it makes them afraid to stand out and pursue their learning desires. Every teacher should work to stop bullying in the classroom by integrating anti-bullying policies and discipline into classroom discipline.